MANAJEMEN EDITING POST PRODUCTION PROGRAM CURRENT AFFAIR DI TVONE - Asse, Ridho Azlam Ambo (Jurnal Visi Komunikasi, 2016)
Management is the art of completing the work through others. In an organization there are various components that are structured and coordinated in the movement toward shared vision and mission. Management is looking for that component to move under coordination, pressure, and problems that hit. Editing management, especially for the current affair type program, has a special purpose. Not just the speed of productivity that is based on the ability of individual editors. This research is done to know the process of stage editor in work. The process of managing files, data management, human resources, tools, facilities, scheduling, until the pattern of editing stage in one of the national media industry. This study concludes that the current affair program management editing system based on the concept of planning, organizing, implementation, supervision, and productivity management is done by Top Down method from top to bottom in the management of currenf affair tvOne editing program. What gets from above during a pre-production meeting of a program. Then coordinate with the supervisor and then delegate down to be implemented according to the agreed plan and in accordance with the duties and functions of both the production team and the editor. Manajemen merupakan seni menyelesaikan pekerjaan melalui orang lain. Dalam sebuah organisasi terdapat berbagai macam komponen yang terstruktur dan terkordinasi dalam gerakan menuju visi dan misi bersama. Manajemen ialah mencari agar komponen tersebut dapat bergerak dibawah koordinasi, tekanan, dan masalah yang menerpa. Manajemen editing khususnya untuk program berjenis current affair, memiliki tujuan khusus. Tidak sekedar kecepatan produktifitas yang didasarkan pada kemampuan individu editor. Penelitian yang dilakukan ini untuk mengetahui proses tahapan editor dalam bekerja. Proses mengelola file, pengelolaan data, sumber daya manusia, alat, fasilitas, penjadwalan, hingga pola tahapan editing pada salah satu industri media skala nasional. Penelitian ini menyimpulkan bahwa sistem manajemen editing program current affair yang berpijak pada konsep perencanaan, pengorganisasian, pelaksanaan, pengawasan, dan manajemen produktivitas adalah dilakukan dengan metode Top Down yaitu dari atas ke bawah pada manajemen editing progam currenf affair tvOne. Apa yang didapat dari atas pada saat rapat pra produksi suatu program. Kemudian berkoordinasi dengan supervisor lalu didelegasikan kebawah untuk dilaksanakan sesuai rencana yang telah disepakati dan sesuai dengan tugas dan fungsi masing-masing baik dari tim produksi dan editor.